Isolation and detection of Burkholderia species in Soil Sample - Pangau, Lua Viana (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Melioidosis may be fatal to the infected human and the animal. Exposure to the soil with high content of Burkholderia pseudomallei may result in fatal infections such as melioidosis. These bacteria dominating a wide range of ecological niches and mainly found in the soil. The prevalence of Burkholderia spp. in soil is high in disturbed areas such paddy field, high water contain soil and the presence of animals.